Anion effects in electrochemical transistors with semiconducting single-walled carbon nanotube networks - Xu, Xuqiang; Fresta, Elisa; Lindenthal, Sebastian; Michel, Edwin; Zaumseil, Jana (ACS applied materials & interfaces, 2025)
Electrochemical transistors (ECTs) rely on the migration of cations or anions toward and into a semiconducting layer under an applied gate bias to counterbalance accumulated electrons or holes and thus control the current flow through the channel. Dense networks of purely semiconducting single-walled carbon nanotubes (s-SWCNTs) are excellent semiconductors for ECTs, as they exhibit very high carrier mobilities, excellent chemical and mechanical stability, and are insoluble in solvents or electrolytes. They are applied here to study the effects of anion size and electrolyte solvent on hole injection and transport in ECTs. We employ electrolyte solutions with chloride and perchlorate, as well as anions based on triflate and fluorinated sulfonyl imides with increasing size and different kosmotropic and chaotropic properties. Significant anion-dependent shifts of the transfer and transconductance curves are evident for aqueous but not organic electrolytes, while the hole mobilities are barely affected. Furthermore, the electrolyte concentration has a strong impact on the ECT characteristics for aqueous electrolytes with large anions. These findings point toward the crucial importance of ion solvation and ionic strength for the formation of electric double layers around hydrophobic carbon nanotubes and thus electrochemical doping of s-SWCNT networks in ECTs.
Online veröffentlicht: 11. Juni 2025
Gesehen am 16.10.2025